Komunikasi Lintas Budaya Dalam Menjaga Toleransi umat Beragama di Kelurahan Sei Kera Hilir II Kecamatan Medan Perjuangan Kota Medan - Erwan Efendi; Winda Kustiawan; Mhd Alpin Azhari Lubis; Iskandar Mubin Dongorang (Peneliti.net, 2023)
Countless different people groups call Indonesia home, giving the nation a rich cultural and religious mosaic. We are a multiethnic and multireligious community, and Indonesians have long had a reputation for being a very spiritual people. At least six faiths are officially acknowledged on a national level in Indonesia, including Christianity, Islam, Hindu Catholicism, Buddhism, and Confucianism. There are a wide variety of faiths practiced in Indonesia, hence its citizens must be tolerant of others who practice different faiths. A tolerant person recognizes the value in the contrasts between themselves and others, as well as between different social groupings. Tolerance is the practice of appreciating and welcoming the variety of human perspectives, customs, faiths, and skin tones that populate our global community. It is crucial to encourage a tolerant mindset not just in the local society, but also outside its borders. When people of different faiths approach one another with an attitude of tolerance, they may help foster an environment where everyone feels safe and respected. The purpose of this research is to analyze the role of cross-cultural communication in sustaining religious tolerance in the community of Sei Kera Hilir II, located in the Medan Perjuangan District of Medan City. Hopefully, the findings of this research may encourage readers of this journal to be more tolerant of people of other faiths and to avoid making assumptions about one another and their beliefs.